2011
DOI: 10.1111/j.1464-410x.2011.10477.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial nephrectomy in two patients with known T3a tumours involving the renal vein

Abstract: Study Type – Therapy (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Although nephron‐sparing surgery (NSS) has became accepted therapy for T1 tumours, radical nephrectony is considered the best therapy for T3a tumours involving the renal vein. NSS can be considered in T3a or greater tumours if imperative indications exist, such as bilateral disease or solitary kidney. However, there is little published data on the characteristics of these patients, the impact of sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…We acknowledge that this experience is rather small, but these cases of imperative partial nephrectomy in conjunction with tumor thrombectomy are extremely rare. In fact, with the exception of a single multi-institutional cohort including a total of 42 patients from 9 different institutions [10], most of the remaining published series comes from single referral centers reporting on the experience obtained from the management of a few cases (Table 1) [19][20][21][22][23]. All these series agree in the technical feasibility of different parenchymal-preserving surgical procedures for cases of intraparenchymal venous branches or main renal vein involvement by the TT.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge that this experience is rather small, but these cases of imperative partial nephrectomy in conjunction with tumor thrombectomy are extremely rare. In fact, with the exception of a single multi-institutional cohort including a total of 42 patients from 9 different institutions [10], most of the remaining published series comes from single referral centers reporting on the experience obtained from the management of a few cases (Table 1) [19][20][21][22][23]. All these series agree in the technical feasibility of different parenchymal-preserving surgical procedures for cases of intraparenchymal venous branches or main renal vein involvement by the TT.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of nephron sparing surgery for T3a or T3b renal cell carcinoma, whether for imperative indications (solitary kidney or renal failure) or intraoperative discovery of the thrombus, showed outcomes that seem acceptable compared to nonconserving surgery [5860]. …”
Section: Discussionmentioning
confidence: 99%
“…Long et al [43] reported OPN in seven solitary kidneys in their series of 49 tumors of at least 7 cm. OPN in patients with a solitary kidney involving renal vein and inferior vena cava has also been reported [44,45]. Liu et al [46] reported on the outcome of patients with a solitary kidney who underwent repeat partial nephrectomy because of recurrence after previous NSS.…”
Section: Extending the Indications Of Partial Nephrectomymentioning
confidence: 93%